Study of the stability of a high-power PV conversion chain for isolated site supply - Akoro Edjadessamam; Bokovi Yao; Agbessi Akueté Pierre; Ateyo Gnakou Mazama (E3S Web of Conferences)
The aim of this paper is to design and study the stability of a 500 kW PV string connected to a DC-AC load. To achieve this, a MPPT method based on a hybrid Artificial Neural Network (ANN)-Synergistic Control Algorithm (SCA) already developed in the literature will be used to find the system's maximum power point. This control will enable the PV generator to deliver maximum energy. Next, the power control approach will be developed to control the inverter, and the stability of the overall system will be studied.